Resonansi verbal dan visual puisi kontemporer karya Aan Mansyur di Instagram: Kajian stilistika - Putri Naufal Nurotul Zannah; Yostiani Noor Asmi Harini; Memen Durachman (Universitas Mulawarman, 2026)
This study discusses Aan Mansyur's digital poem entitled TETAPI, TIDAK uploaded via the Instagram account @apoetographer. The background of this study stems from the phenomenon of poetry that combines literary style and visual elements on Instagram. The purpose of this study is to reveal how literary style as a verbal aspect and visual aspect of poetry resonate. The method used is descriptive qualitative with a stylistic approach by Pradopo (2021). The results show that Aan Mansyur uses language style to emphasise social criticism and moral awareness. The visual element of purple-green colour gradation reinforces the reflective and contemplative atmosphere. The conclusion of this study confirms that Aan Mansyur's digital poetry presents verbal and visual resonance, namely the harmony between the power of language and visual elements that reinforce each other in building an aesthetic experience. This resonance shows the transformation of the function of poetry in the digital era from a mere medium of expression to a reflective, empathetic, and humanistic space that unites words and colours in a single contemporary aesthetic consciousness.